N??vel de servi??o de log??stica, confian??a e inten????o de permanecer no relacionamento: uma an??lise em neg??cios business-to-business - Papis, Marcos Mellone (2009)
Trust has been studied over time under different perspectives which embrace interpersonal relationships within commercial environment. Trust and commitment present in a commercial relationship assume a continuous repurchase intention. On the other hand, in a commercial environment, considerations about the impact that logistics is capable of carrying out have been discussed under technical and objective aspects. Intention to stay in a commercial relationship presumes its maintenance and trust takes place in this discussion. As main objective, this research proposed to verify how supplier logistics performance impacts trust of her client company in the light of relationship level these companies share together in a long term oriented commercial relationship. Research methodology applied is exploratory qualitative, being data collection accomplished via interviews with buyers from such companies who have autonomy to decide for a commercial relationship maintenance. Interviews were based on previous studies about trust in commercial relationship and opened questions were built to cover this activity. A national company of consumer goods with 2 billions of reais annual revenues was selected to provide the sample under convenience. It was verified by the presented data that basically the transparency in communication is valued, conflicts do not imply on relationship progress as a certainty and despite logistics is considered important as a support to this relationship, it is not able to interrupt this relationship, regardless its performance level. As conclusion, low logistics performance level wears down commercial relationship while high performance level only helps repurchase intention. Research limitation, based on size and type of chosen sample, opens opportunity for further verification of this issue.